Omicron (B.1.1.529) BA.1 or BA.2-related effects on immune responses in previously naïve versus imprinted individuals: immune imprinting as an advantage in the humoral immune response against novel variants - Sonnleitner, Sissy Therese; Walder, Samira; Knabl, Ludwig; Poernbacher, Roswitha; Tschurtschenthaler, Thomas; Hinterbichler, Eva; Sonnleitner, Stefanie; Muehlmann, Viktoria; Posch, Wilfried; Walder, Gernot (Frontiers in Immunology, 2023)
Background Immune imprinting is a phenomenon in which a person's immune system develops a specific immunological memory of the pathogen or vaccine due to a previous exposure. This memory basically leads to a faster and stronger immune response in a subsequent contact to the same pathogen or vaccine. However, what happens if the pathogen has changed considerably in the meantime due to mutations in the main target region of antibodies, as in the evolution of SARS-CoV-2 from the ancestral strain to B.1.1.529 (Omicron)? In this case, does immune imprinting also confer an advantage in repeated contact and does it lead to a stronger immune response? Methods To clarify these questions, we investigated the effects of immune imprinting in the context of SARS-CoV-2 by comparing a group of previously infection-naïve versus imprinted study participants and determined differences in humoral and cellular immune responses during and after infection with strain SARS-CoV-2 B.1.1.529 BA.1 and BA.2, respectively. We used a commercial CLIA, immunoblots, IFN-γ ELISpots and a plaque-reduction neutralization test to generate a clear and comparable picture of the humoral and cellular immune response in the two study groups. Results Imprinted participants developed significantly higher antibody titers and showed significantly stronger neutralization capacity against the ancestral strain, BA.1 and BA.5. The immune response of naïve study participants was narrower and related mainly to the receptor-binding domain, which resulted in a lower neutralization capacity against other strains including BA.5. Naïve study participants showed a significantly higher cellular immune response than the imprinted study group, indicating a higher antigenic challenge. The cellular immune response was directed against general structures of SARS-CoV-2 and not specifically against the receptor-binding domain. Conclusion Viral variant infection elicits variant-specific antibodies and prior mRNA vaccination or infection with a previous SARS-CoV-2 variant imprints serological responses toward the ancestral strain rather than variant antigens. On the other hand, our study shows that the initially higher specific antibody titers due to former imprinting via vaccination or prior infection significantly increased the humoral immune response, and therefore outperformed the humoral immune response of naïve study participants.